Single-step, DC thermal plasma-assisted synthesis of Ag-C nanocomposites with less than 10 nm sizes for antibacterial applications. (23rd June 2020) - Sabavath, Gopikishan; Rahman, Mizanur; Sarmah, Trinayan; Dihingia, Pubali; Srivastava, Divesh N; Sharma, Swati; Pandey, L M; Kakati, M
Abstract: A single-step, thermal plasma-assisted technique is reported for size-controlled synthesis of silver-carbon (Ag-C) nanocomposites, to be used for antibacterial applications. Silver nanoparticles of sizes less than 10 nm can directly penetrate into the core of the bacteria, while stiff, nanocrystalline carbon may rupture the microorganisms with their sharp edges. Experiments demonstrated that silver nanoparticles nucleate anchoring tightly on carbon sheets, which can inhibit their aggregation and growth in size and becomes more effective as crystallinity of the carbon enhances further. Nanocomposite samples were synthesized using a hot graphite nozzle and with variation of ambient pressure in the sample collection chamber. The Ag-C sample synthesized at 190 mbar chamber pressure demonstrated the best antibacterial activities. The zone of inhibition was measured for this sample as 18 mm for the gram-positive E. hirae and 15 mm for the gram-negative E. coli bacteria at their corresponding minimum inhibitory values of 0.54 mg ml −1 and 0.9 mg ml −1 respectively. The crystallinity of the carbon nanosheets was measured to be the best for this particular sample and the average size of the silver nanoparticles remaining entangled on them was measured as 4.6 nm, which to our knowledge is the smallest ever synthesized by a plasma-assisted method. The gas temperature at the injection section was measured using the C2 Swan band system, (0, 0) vibrational transition located at 516.5 nm, which confirms temperature enhanced substantially in presence of the graphite nozzle, which had led to the enhanced material crystallinity and synthesis of particles with the smallest sizes.